Value addition to local Kani tribal knowledge: patenting, licensing and benefit-sharing - Anil K Gupta
The subject of this case study is the role of intellectual property rights in the benefit-sharing arrangements concerning the "Jeevani" drug, which was developed by scientists at the Tropical Botanic Garden and Research Institute (TBGRI), based on the tribal medicinal knowledge of the Kani tribe in Kerala, South India. "Jeevani" is a restorative, immunoenhancing, anti-stress and anti-fatigue agent, based on the herbal medicinal plant arogyapaacha, used by the Kani tribals in their traditional medicine. Within the Kani tribe the customary rights to transfer and practice certain traditional medicinal knowledge are held by tribal healers, known as Plathis. The knowledge was divulged by three Kani tribal members to the Indian scientists who isolated 12 active compounds from arogyapaacha, developed the drug "Jevaani", and filed two patent applications on the drug (and another patent based on the same plant but for different use). The technology was then licensed to the Arya Vaidya Pharmacy, Ltd., an Indian pharmaceutical manufacturer pursuing the commercialization of Ayurvedic herbal formulations. A Trust Fund was established to share the benefits arising from the commercialization of the TK-based drug "Jevaani". The operations of the Fund with the involvement of all relevant stakeholders, as well as the sustainable harvesting of the arogyapaacha plant, have posed certain problems which offer lessons on the role of intellectual property rights in benefit-sharing over medicinal plant genetic resources and traditional medicinal knowledge